Genomic Analysis for the Detection of Bleeding and Thrombotic Disorders - Gomez, Keith (Seminars in Thrombosis and Hemostasis, 2021)
The development of high-throughput sequencing technologies has ushered in a new era of genomic testing in clinical medicine. This has greatly enhanced our diagnostic repertoire for hemostatic diseases particularly for milder or rarer bleeding disorders. New genetic causes for heritable platelet disorders have been discovered along with the recognition of clinical manifestations outside hemostasis, such as the association of leukemia with RUNX1 variation. Genome-wide association studies in heritable thrombophilia have demonstrated that some of the genetic variants that are commonly included in thrombophilia testing are of no clinical relevance, while uncovering new variants that should potentially be included. The implementation of new technology has necessitated far-reaching changes in clinical practice to deal with incidental findings, variants of uncertain significance, and genetic disease modifiers. Mild bleeding disorders that were previously considered to have a monogenic basis now appear to have an oligogenic etiology. To harness these advances in knowledge large databases have been developed to capture the new genomic information with phenotypic features on a population-wide scale. The use of this so-called “big data” requires new bioinformatics tools with the promise of delivering precision medicine in the foreseeable future. This review discusses the use of these technologies in clinical practice, the benefits of genomic testing, and some of the challenges associated with implementation.
Keywords: inherited bleeding disorders; heritable platelet disorders; heritable thrombophilia; genetic testing; genetic reporting; genetic interpretation; genomic analysis; big data; bioinformatics